Iron‐biomineralizing organelle in magnetotactic bacteria: function, synthesis and preservation in ancient rock samples. (22nd June 2020) - Amor, Matthieu; Mathon, François P.; Monteil, Caroline L.; Busigny, Vincent; Lefevre, Christopher T.
Summary: Magnetotactic bacteria (MTB) are ubiquitous aquatic microorganisms that incorporate iron from their environment to synthesize intracellular nanoparticles of magnetite (Fe3 O4 ) or greigite (Fe3 S4 ) in a genetically controlled manner. Magnetite and greigite magnetic phases allow MTB to swim towards redox transition zones where they thrive. MTB may represent some of the oldest microorganisms capable of synthesizing minerals on Earth and have been proposed to significantly impact the iron biogeochemical cycle by immobilizing soluble iron into crystals that subsequently fossilize in sedimentary rocks. In the present article, we describe the distribution of MTB in the environment and discuss the possible function of the magnetite and greigite nanoparticles. We then provide an overview of the chemical mechanisms leading to iron mineralization in MTB. Finally, we update the methods used for the detection of MTB crystals in sedimentary rocks and present their occurrences in the geological record.